"Castelao e a sua época"’s censorship - Iglesias Mira, Antonio (Madrygal. Revista de Estudios Gallegos, 2014)
Castelao e a sua época was the second show that Ricard Salvat prepared with CITAC during the 68/69´s theater season, which coincides with the “Crise Académica de 69”. These show does not get to perform because it was prohibited by the censor´s office and, then, the political police expeled Salvat from the country. In this essay we briefly present what happened during the Salvat´s stay and analize the censorship´s marks on Castelao e a sua época’s dramatic text.